3D printed-electrospun PCL/hydroxyapatite/MWCNTs scaffolds for the repair of subchondral bone. (14th December 2022) - Cao, Yanyan; Sun, Lei; Liu, Zixian; Shen, Zhizhong; Jia, Wendan; Hou, Peiyi; Sang, Shengbo
Abstract: Osteochondral defect caused by trauma or osteoarthritis exhibits a major challenge in clinical treatment with limited symptomatic effects at present. The regeneration and remodeling of subchondral bone play a positive effect on cartilage regeneration and further promotes the repair of osteochondral defects. Making use of the strengths of each preparation method, the combination of 3D printing and electrospinning is a promising method for designing and constructing multi-scale scaffolds that mimic the complexity and hierarchical structure of subchondral bone at the microscale and nanoscale, respectively. In this study, the 3D printed-electrospun poly(ɛ-caprolactone)/nano-hydroxyapatites/multi-walled carbon nanotubes (PCL/nHA/MWCNTs) scaffolds were successfully constructed by the combination of electrospinning and layer-by-layer 3D printing. The resulting dual-scale scaffold consisted of a dense layer of disordered nanospun fibers and a porous microscale 3D scaffold layer to support and promote the ingrowth of subchondral bone. Herein, the biomimetic PCL/nHA/MWCNTs scaffolds enhanced cell seeding efficiency and allowed for higher cell–cell interactions that supported the adhesion, proliferation, activity, morphology and subsequently improved the osteogenic differentiation of bone marrow mesenchymal stem cells in vitro . Together, this study elucidates that the construction of 3D printed-electrospun PCL/nHA/MWCNTs scaffolds provides an alternative strategy for the regeneration of subchondral bone and lays a foundation for subsequent in vivo studies. Graphical abstract: